Pendidikan Berbasis Merdeka Belajar - Ahmad Darlis; Ali Imran Sinaga; Musthafa Fadil Perkasyah; Lisa Sersanawawi; Isnayni Rahmah (Program Pascasarjana UIN Sumatera Utara, 2022)
The attraction of learning independence is the freedom of educators and students in teaching and learning activities. This is something that is not experienced by educators because they prioritise educational administration in learning. Many teachers do not really understand their role and function as teachers in this latest curriculum. In the world of education, making an innovation is a must in order to bring quality changes to schools and students. In this case, teachers can develop the creativity of students by giving them the opportunity to determine the theme or material and what activities will be carried out during the learning process. Innovative learning is expected to create a liberating learning climate.